Uso de resíduos de frutas para produção de álcool em gel como alternativa para o ensino de funções orgânicas oxigenadas - Sousa, Sandra Inês de Mattia de (2023)
To foster student interest and engagement in the teaching of chemistry, contextualization, and the use of active methodologies in the approach to content are necessary. Therefore, this work aimed to stimulate the investigative character of students in teaching oxygenated organic functions, through the development of an educational product, by producing hand sanitizer from fruit waste generated in the school kitchen, as well as the elaboration and validation of a didactic sequence involving Project-Based Learning, in the Chemistry discipline for High School. The methodology consisted of the elaboration, development, and evaluation of a didactic sequence, organized into four units, totaling 12 classes, involving quantitative and qualitative exploratory research, written production, and a final questionnaire, with concepts of organic chemistry, experimentation, and other activities. In the end, this didactic sequence was evaluated by teachers and students, collecting impressions and suggestions for improving the work. The results indicated that the elaboration and use of the didactic sequence, mediated by the active methodology, Project-Based Learning (PBL), as well as experimentation, promoted engagement, fostered interest, and stimulated the investigative character of the students, which can be observed by the indications that learning happened significantly.